2021
DOI: 10.1021/acsaelm.1c00969
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Energy Conversion Efficiency via Interfacial Carrier Diffusion in Microscale Segmented Thermoelectric Materials

Abstract: Explicit carrier diffusion may play a significant role in energy conversion of nano-and microscale segmented thermoelectric (TE) devices because of the combined effect of the diffusion induced and Seebeck effect induced currents near the segment interfaces. This work presents a computational thermoelectricity model with diffusion current to investigate carrier diffusion across the interface in a microscale segmented n-type TE material and its influence on the TE energy conversion efficiency. The carrier concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Carrier transport plays a significant role in determining TE properties and energy conversion efficiency. [23][24][25][26] Lu et al [24,25] developed a transport model for the Seebeck coefficient of organic TEs and reviewed the progress in carrier transport theory for organic semiconductors. Jin and Yang [26] showed that the explicit carrier diffusion across the segment interface in a segmented TE material may significantly increase the TE energy conversion efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carrier transport plays a significant role in determining TE properties and energy conversion efficiency. [23][24][25][26] Lu et al [24,25] developed a transport model for the Seebeck coefficient of organic TEs and reviewed the progress in carrier transport theory for organic semiconductors. Jin and Yang [26] showed that the explicit carrier diffusion across the segment interface in a segmented TE material may significantly increase the TE energy conversion efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Lu et al [24,25] developed a transport model for the Seebeck coefficient of organic TEs and reviewed the progress in carrier transport theory for organic semiconductors. Jin and Yang [26] showed that the explicit carrier diffusion across the segment interface in a segmented TE material may significantly increase the TE energy conversion efficiency. A first-order linear theory will be developed in a future study to examine if a linear theory will also be accurate when explicit carrier diffusion is included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations